PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN - Tiara Puspa Sari; Sri Ekowati ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2022)
This study entitled The Effect of Rewards and Punishment on Employee Performance (Case Study at PT. Bukit Angkasa Makmur Bengkulu). The formulation of the problem in this study is whether the giving of rewards has a significant effect on employee performance at PT. Bukit Angkasa Makmur Bengkulu. Does the provision of punishment significantly influence the performance of employees at PT. Bukit Angkasa Makmur Bengkulu. Does the giving of reward and punishment simultaneously affect the performance of employees at PT. Bukit Angkasa Makmur Bengkulu. This research was conducted on employees of the Production Department of PT. Bukit Angkasa Makmur Bengkulu. While the time of this research was conducted for 1 month, namely on January 1, 2021 to February 1, 2021. The population of this study were employees at PT. Bukit Angkasa Makmur Bengkulu, while the sample of this study were employees of the Production Department of PT. Bukit Agkasa Makmur Bengkulu, amounting to 113 people. This means that the sample material uses quantitative methods. With the research test data analysis technique, the results of the study can be concluded that the respondent's perception of reward (X1), Punishment (X2) has an effect on performance (Y) with the results of multiple linear regression, the following equation is obtained: X2) 0.117 and the coefficient of determination R2 = 0.036 or approximately (3.6%) through hypothesis testing jointly (simultaneously) and individually (partially) in this study using the f test and t test, Reward (X1) , Punishment (X2) = 0.000, it means that the value of fsig <0.05 shows a concurrent and significant effect.